Draft Annual Plan 1988-89 Volume X Government of Assam - Planning Commission (Planning Commission, 1988)
During seventh plan (1985-90) it was proposed to provide 800 additional posts of L.P. teachers to open new L.P. Schools in school less villages and double teachers to single teacher L.P. Schools. Out of 800 posts 200 posts have been provided during the year 1985-86, 20 eligible ad-hoc M.E. schools have also been provincialised during that year. Moreover financial assistance has been extended for maintenance of adhoc M.E. schools.
Government of Assam
Government of Assam